Preparation and Characterization of Styrene Bearing Diethanolamine Side Group, Styrene Copolymer Systems, and Their Metal Complexes - Acikses, Aslisah; Comez, Necmittin; Biryan, Fatih (Hindawi Ltd, 2018)
The two copolymer systems of styrene bearing diethanol amine side group and styrene were prepared by free radical polymerization method at 60 degrees C in presence of 1,4-dioxane as solvent and AIBN as initiator. Their metal complexes were prepared by reaction of the copolymer used as ligand P(DEAMSt-co-St)L '' and Ni(II) and Co(II) metal ions, which was carried out in presence of ethanol and NaOH at 65 degrees C for 48 h in pH = 7.5. The structures of the copolymers used as ligand and metal complexes were identified by FT-IR, H-1-NMR spectra, and elemental analysis. The properties of the copolymers used as ligand and metal complexes were characterized by SEM-EDX, AAS, DSC, TGA, and DTA techniques. Then, the electrical properties of the copolymers and metal complexes were examined as a function of the temperature and frequency, and the activation energies (E-a) were estimated with conductivity measurements.
Keywords: Ion-Exchange-Resins; Chelating Polymer; Dielectric-Properties; Thermal-Degradation; Conductivity; Cu(Ii); Acid; Behavior; Sorption; Removal